Towards a re-definition of development : essays and discussion on the nature of development in an international perspective - Birou, Alain; Henry, Paul-Marc.; Schlegel, John P. (Oxford ; New York : Published for the Development Centre of the Organisation for Economic Co-operation and Development by Pergamon Press, 1977)
This book is on development, its definition and types
oo 30/08/2018
Loans
Keywords: Economic development; Social change; Developing countries